Insights into preventive measures for dental erosion - Ana Carolina Magalhães; Annette Wiegand; Daniela Rios; Heitor Marques Honório; Marília Afonso Rabelo Buzalaf (University of São Paulo, 2009)
Dental erosion is defined as the loss of tooth substance by acid exposure not involving bacteria. The etiology of erosion is related to different behavioral, biological and chemical factors. Based on an overview of the current literature, this paper presents a summary of the preventive strategies relevant for patients suffering from dental erosion. Behavioral factors, such as special drinking habits, unhealthy lifestyle factors or occupational acid exposure, might modify the extent of dental erosion. Thus, preventive strategies have to include measures to reduce the frequency and duration of acid exposure as well as adequate oral hygiene measures, as it is known that eroded surfaces are more susceptible to abrasion. Biological factors, such as saliva or acquired pellicle, act protectively against erosive demineralization. Therefore, the production of saliva should be enhanced, especially in patients with hyposalivation or xerostomia. With regard to chemical factors, the modification of acidic solutions with ions, especially calcium, was shown to reduce the demineralization, but the efficacy depends on the other chemical factors, such as the type of acid. To enhance the remineralization of eroded surfaces and to prevent further progression of dental wear, high-concentrated fluoride applications are recommended. Currently, little information is available about the efficacy of other preventive strategies, such as calcium and laser application, as well as the use of matrix metalloproteinase inhibitors. Further studies considering these factors are required. In conclusion, preventive strategies for patients suffering from erosion are mainly obtained from in vitro and in situ studies and include dietary counseling, stimulation of salivary flow, optimization of fluoride regimens, modification of erosive beverages and adequate oral hygiene measures.